Prevalence of phantom phenomena in congenital and early-life amputees - Diers, Martin; Fuchs, Xaver; Bekrater-Bodmann, Robin; Flor, Herta (The journal of pain, 2023)
Phantom limb pain (PLP) is a common consequence of the amputation of a limb. Persons with congenital limb absence (congenital amputees) or an acquired limb amputation at an early age seem to rarely experience PLP. However, the number of available studies and their sample sizes are low. In the present cross-sectional study, we assessed the presence of several phantom phenomena in a sample of 99 adult unilateral congenital amputees (con) of whom 34 had a limb correction later in life (limbc) and 153 adult participants with a unilateral amputation before the age of 6 years (subgroups: amputation between birth and 2 years (0-2y; n = 48), 3-4 years (3-4y; n = 46), and 5 to 6 years (5-6y; n = 59)). We found a higher prevalence and intensity of PLP in the 5-6y group compared to the other groups. Residual limb pain (RLP) intensity was higher in the 3 to 4 y and 5 to 6 y groups compared to the con group. Non-painful phantom limb sensation (PLS) intensity and telescoping intensity were higher in the 5 to 6 y group compared to the con and 0 to 2 y groups. Our results indicate that PLP prevalence as well as intensity is low when the limb loss happened before the age of 5 years. - Perspective - The prevalence of phantom limb pain, residual limb pain, and non-painful phantom limb sensation in congenital amputees and participants with an amputation early in life is low. This might be due to the missing or reduced nociceptive input from the residual limb to the brain and higher development-associated adaptability of the somatosensory system.